Study on Torque Distribution of Torque Split Transmission System of Face Gear - Peng Xianlong; Zhang Le (Jixie chuandong)
In order to research the influence of installation errors and support deformations on load distribution in the torque split transmission system of face gear,a calculating method for load distribution of torque split transmission system of face gear is proposed. At first,the model of load sharing for torque split transmission system of face gear is established by torque balance equation and deformation compatibility condition,and the deformation compatibility condition directly relate to time- vary meshing stiffness of gear pair. Secondly,the force on the face gear is analyzed,and the form that the deformation of support system is described,the support deformation is translated to errors of gear. Thirdly,the meshing stiffness of gear pair is fit as function of load by tooth contact analysis（ TCA） and loaded tooth contact analysis（ LTCA）. At last,the calculation method for coefficients of load sharing is proposed. Numerical example demonstrates that the coefficients of two path in the system is respectively 0. 65 and 1. 35 under the combined effects of installation errors and support deformation,while the radial support deformation ax1 of the pinion is- 692. 3 μm,the coefficients of the two path is respectively 0. 987 0 and 1. 013. Hence,the radial elastic support ax1 of the pinion,to some extent,is able to offset the influence of unequal torque splitting caused by installation errors and support deformation.